Supplementation of tempeh extract for improving quality of bone in premenopausal conditions using rats as animal models - . Safrida; Nastiti Kusumorini; Wasmen Manalu; Hera Maheshwari (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
Tempeh extract is a natural substance that contains phytoestrogens, having similar estrogen activity. This study was designed to determine the potential of tempeh extract in improving the quality bone in premenopausal conditions, and to compare the natural product of tempeh extract with commerciallyavailable hormones (genistein, ethinylestradiol, and somatotropin). Experimental design used was Completely Randomized Design (CRD) consisted of 7 experimental groups, each consisted of 3 rats i.e.,1) K= premenopausal rats as a negative control, 2) P = premenopausal rats given distilled water orally as a placebo, 3) TEM = premenopausal rats given tempeh extract 300 mg/day/200g body weight, 4) GEN =premenopausal rats given genistein 0.25 mg/day/kg body weight, 5) EST = premenopausal rats givenethinylestradiol 9x10-3 mg/day/200g body weight, 6) SO = premenopausal rats injected with sesame oil/day/kg body weight, 7) BST = premenopausal rats injected somatotropin 9 mg/day/kg body weight. The parameters observed were the bone and serum calcium and phosphorus concentrations, bone ashconcentrations, bone collagen concentrations, bone water concentrations, bone RNA concentrations, bone length, bone weight, bone density, and bone strength. Supplementations of tempeh extract for two months in premenopausal rats could improve the quality of bone, which was characterized by the increased bone calcium concentrations, ratio of Ca/P on tibia bone, bone ash levels, bone density, and bone strength